Projeto de estabilização estrutural das paredes de apoio da abóbada central da Igreja de Santa Teresa - Muñoz, R. (Revista ALCONPAT, 2014)
The Church and Convent of Santa Teresa, dating from the second half of the seventeenth century and located in Salvador, Bahia, Brazil, comprise an important architectural complex listed by the Instituto do Patrimônio Histórico e Artístico Nacional. The Church presents an architecture style between the Renaissance and Baroque, with interior of the eighteenth century. The roof of its central aisle consists of a dome, brick masonry arches carved stone on which rests on freestanding walls, built in stone masonry, presenting cracks and without plumb. After detailed analysis it was concluded that these damages occur due to the horizontal thrust exerted by the dome. The objective of this paper is to present the solution to stabilize the walls supporting the central dome using metal rods. Results present the design details of stabilizing walls and technique used to contain the lack of plumb. Keywords: heritage, stability, structure, rods.